New strong divisibility sequences - Du, Zhibin (Ars mathematica contemporanea, 2022)
We provide new families of divisibility and strong divisibility sequences based on some factorization properties of Chebyshev polynomials.
Keywords: chebyshev polynomials; determinant; strong divisibility sequences; tridiagonal matrices